Polycyclic aromatic hydrocarbon (PAH) formation during acetylene pyrolysis in tubular reactor under low pressure carburizing conditions. (20th July 2019) - Bensabath, Tsilla; Le, Minh Duy; Monnier, Hubert; Glaude, Pierre-Alexandre
Graphical abstract: Highlights: Experiments of acetylene pyrolysis at 1173 K and 8 kPa in a tubular reactor. Analysis of products including the 16 EPA-PAHs. PAH amounts increase with residence time at low acetylene concentration. PAH amounts slightly decrease with residence time for pure acetylene. Correct agreement with simulation results, especially for the main products. Abstract: Low-pressure carburizing involves hydrocarbon pyrolysis, which leads to a fast gas-phase formation of polycyclic aromatic hydrocarbons (PAHs), some of which, such as benzo[ a ]pyrene, are carcinogenic. Workers can be exposed to these PAHs during maintenance and cleaning operations of carburizing furnaces. Experiments of acetylene pyrolysis were carried out in conditions close to low-pressure gas carburizing processes, at 1173 K and 8 kPa, in tubular reactors. At the outlet of the reaction zone, the reactant and the reaction products were analyzed by gas chromatography (TCD, FID and MS). Amongst other products, 16 PAHs classified as priority pollutants by the United States Environmental Protection Agency (US EPA) were observed and quantified. The study of the influence of residence time and of inlet reactant concentration shows that amounts of PAHs increase with residence time at low acetylene concentration but slightly decrease with pure acetylene due to the conversion of PAHs into soot. Results were compared to simulation results obtained with a detailed kinetic model of light hydrocarbon pyrolysis.